The Influence of Pandawa Beach Festival on Tourists' Decisions to Revisit Pandawa Beach - Anik Suryaningsih, Ni Kadek Anik Suryaningsih; I Gusti Agung Suprastayasa; Nyoman Reni Ariasri (Jurnal Pariwisata Nusantara (JUWITA), 2024)
Purpose: The objective of this study is to identify and assess the impact of the Pandawa Beach Festival on tourists' decisions to revisit Pandawa Beach. Method: This research employed both quantitative and qualitative data collected from 100 respondents through questionnaires to evaluate the effect of the Pandawa Beach Festival on tourists' decisions to return to Pandawa Beach. The study was conducted at Pandawa Beach, Bali, and the data were analyzed using simple linear regression. Validity and reliability tests, classical assumption tests, and the coefficient of determination were utilized to ensure the accuracy and evaluation of the model. The results indicated that the Pandawa Beach Festival significantly influences tourists' decisions to revisit Pandawa Beach. Result: The findings of this study show that the Pandawa Beach Festival has a positive and significant impact on the decision to revisit, with a t-value of 13.28 > t-table value of 1.689. This indicates that the Pandawa Beach Festival (X) has a significant influence on the Decision to Revisit (Y). The coefficient of determination test results show that the dependent variable is explained by the independent variable by 64.3%, while the remaining 35.7% is influenced by other variables not included in this study. Contribution: These findings can serve as a foundation for tourism destination managers to design more effective marketing strategies and enhance the role of festival events in attracting tourist visits.